Effective refractive error coverage in adults aged 50 years and older: estimates from population-based surveys in 61 countries - Bourne, Rupert; Cicinelli, Maria Vittoria; Sedighi, Tabassom; Tapply, Ian H; McCormick, Ian; Jonas, Jost B.; Congdon, Nathan G; Ramke, Jacqueline; Naidoo, Kovin S; Fricke, Timothy R; Burton, Matthew J; Müller, Andreas; et al. (The lancet. Global health, 2022)
Background - In 2021, WHO Member States endorsed a global target of a 40-percentage-point increase in effective refractive error coverage (eREC; with a 6/12 visual acuity threshold) by 2030. This study models global and regional estimates of eREC as a baseline for the WHO initiative. - Methods - The Vision Loss Expert Group analysed data from 565 448 participants of 169 population-based eye surveys conducted since 2000 to calculate eREC (met need/[met need + undermet need + unmet need]). A binary logistic regression model was used to estimate eREC by Global Burden of Disease (GBD) Study super region among adults aged 50 years and older. - Findings - In 2021, distance eREC was 79·1% (95% CI 72·4-85·0) in the high-income super region; 62·1% (54·7-68·8) in north Africa and Middle East; 49·5% (45·0-54·0) in central Europe, eastern Europe, and central Asia; 40·0% (31·7-48·2) in southeast Asia, east Asia, and Oceania; 34·5% (29·4-40·0) in Latin America and the Caribbean; 9·0% (6·5-12·0) in south Asia; and 5·7% (3·1-9·0) in sub-Saharan Africa. eREC was higher in men and reduced with increasing age. Global distance eREC increased from 2000 to 2021 by 19·0%. Global near vision eREC for 2021 was 20·5% (95% CI 17·8-24·4). - Interpretation - Over the past 20 years, distance eREC has increased in each super region yet the WHO target will require substantial improvements in quantity and quality of refractive services in particular for near vision impairment. - Funding - WHO, Sightsavers, The Fred Hollows Foundation, Fondation Thea, Brien Holden Vision Institute, Lions Clubs International Foundation.
Online verfügbar: 11. Oktober 2022, Artikelversion: 16. November 2022
Gesehen am 27.08.2024
Mitglieder des Vision Loss Expert Group of the Global Burden of Disease Study: Alain Bron, Ching-Yu Cheng, Arthur Fernandes, David Friedman, Andrew Gazzard, Rim Kahloun, John Kempen, Moncef Khairallah, Van C Lansingh, Janet Leasher, Nicolas Leveziel, Hans Limburg, Michal Nowak, Konrad Pesudovs, Tunde Peto, Luca Rossetti, Nina Tahhan, Rohit Varma, Wondu Alemayehu, Aries Arditi, Reza Dana, Monte Del Monte, jenny Deva, Laura Dreer, Josh Ehrlich, Leon Ellwein, Billy Hammond, Mary E Hartnett, April Ingram, Rohit Khanna, Judy Kim, Jennifer Lim, Alan Morse, David Musch, Maurizio B Parodi, Pradeep Ramulu, Alan Robin, Janet Serle, Tueng Shen, Rita S Sitorus, Dwight Stambolian, Fotis Topouzis, Miltiadis Tsilimbaris, Gianni Virgili, Sheila West
Mitglieder der The RAAB International Co-Author Group: Jafer K Ababora, Heba AlSawahli, Hery Harimanitra Andriamanjato, Rosario Barrenechea, Juan F Batlle, Anthea M Burnett, Robert P Finger, Marcelo Gallarreta, Pedro A Gomez-Bastar, Reeta Gurung, Elesh Jain, George E Kabona, Khumbo Kalua, Levi Kandeke, Jefitha Karimurio, Susan A Kikira, Sucheta Kulkarni, Van C Lansingh, Wanjiku Mathenge, Sailesh Kumar Mishra, Seyed Farzad Mohammadi, Manfred Mörchen, Nasiru Muhammad, Grace C Mutati, Maria Eugenia Nano, János Németh, Ala Paduca, Alexander Páez, M Mansur Rabiu, Lutfah Rif'ati, Mohamad Aziz Salowi, Yuddha D Sapkota, Nicholas Sargent, Ubeydulla Thoufeeq, Astrid V Villalobos, Biaxiang Xiao, Mariano Yee Melgar, Xiu Juan Zhang